2021
DOI: 10.1063/5.0046429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effectiveness of optimum physical distancing phenomena for COVID-19

Abstract: Currently, COVID-19 is a global pandemic that scientists and engineers around the world are aiming to understand further through rigorous testing and observation. This paper aims to provide safe distance recommendations among individuals and minimize the spread of COVID-19, as well as examine the efficacy of face coverings as a tool to slow the spread of respiratory droplets. These studies are conducted using computational fluid dynamics analyses, where the infected person breathes, coughs, and sneezes at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…According to him, a distance of 120 cm to 350 cm is considered as the category of social distance which can be varied in terms of sensational perception due to the increasing physical distance. Although simulation studies have delineated that the measurement of the standard social distance is variable depending on different environmental circumstances, it is recommended to observe 110 cm physical distance in case of the existence of a gentle breeze ( Chea et al, 2021 ). Nowadays, people have been asked to maintain a social distance, not to bring people into their own personal territory, transfer their tasks into indoor activities (remote working), and stay in their neighborhoods as much as possible.…”
Section: The Balance Between Social Distancing and Social Interactionmentioning
confidence: 99%
“…According to him, a distance of 120 cm to 350 cm is considered as the category of social distance which can be varied in terms of sensational perception due to the increasing physical distance. Although simulation studies have delineated that the measurement of the standard social distance is variable depending on different environmental circumstances, it is recommended to observe 110 cm physical distance in case of the existence of a gentle breeze ( Chea et al, 2021 ). Nowadays, people have been asked to maintain a social distance, not to bring people into their own personal territory, transfer their tasks into indoor activities (remote working), and stay in their neighborhoods as much as possible.…”
Section: The Balance Between Social Distancing and Social Interactionmentioning
confidence: 99%
“…With respect to the third group of factors, several studies analyse weather conditions, such as temperature [ 30 ], humidity or precipitations [ 30 33 ], daylights hours [ 31 34 ], wind speed [ 31 , 32 , 35 ] or air pollution [ 1 ]. The weather conditions are deeply interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…The last analysed factor is the wind speed, which increases the number of cases and deaths [ 31 ]. The improper airflow and higher wind velocity can strongly increase the travelling distance of aerosol particles and droplets, the needed social distancing, and the risk of Coronavirus transmission [ 32 , 35 ]. A limitation to the increase of virus spread generated by the wind is the wearing face coverings (generally masks).…”
Section: Introductionmentioning
confidence: 99%
“…CFD (computational fluid dynamics) studies performed in an indoor environment 27,31,32,39,40 and outdoors 33 found similar conclusions regarding the physical distancing measures. The effect of masks on disease transmission was analyzed in several studies 32,41,42 concluding that masks can cut the droplet transmission distance significantly by suppressing the exhaled flow as well as altering the size distribution of the exhaled droplets. As mentioned, the presence of wind was also seen to assist the exhaled flow and consequently increase the distances over which the infection can be transmitted both with or without a mask.…”
Section: Introductionmentioning
confidence: 99%